Survey of hardware protection of design data for integrated circuits and intellectual properties. Issue 6 (1st November 2014) - Colombier, Brice; Bossuet, Lilian
Abstract : This study reviews the current situation regarding design protection in the microelectronics industry. Over the past 10 years, the designers of integrated circuits (IC) and intellectual properties (IP) have faced increasing threats including counterfeiting, reverse‐engineering and theft. This is now a critical issue for the microelectronics industry, mainly for fabless designers and IP designers. Coupled with increasing pressure to decrease the cost and increase the performance of ICs, the design of a secure, efficient, lightweight protection scheme for design data is a serious challenge for the hardware security community. However, several published works propose different ways to protect design data including functional locking, hardware obfuscation and IC/IP identification. This study presents a survey of academic research on the protection of design data. It concludes with the need to design an efficient protection scheme based on several properties.